2022
DOI: 10.1515/bejm-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Effects of Private Debt on Income Growth

Abstract: This paper uses a panel vector autoregressive model to study the differential effects of components of private debt on income growth for a large panel of countries. While household debt growth in a given period generally has a positive impact on income, this effect is much stronger for countries with relatively lower levels of income and household debt-to-GDP ratios. On the other hand, the responsiveness of income growth to an increase in corporate debt varies across countries, with a consistently negative imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…These conclusions are further confirmed by robustness tests, and these results correspond with the initial hypothesis. This paper's research results agree with those of literature, such as Liaqat and Ahmed [26] and Wei [30], and show that the methods are robust and stable.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These conclusions are further confirmed by robustness tests, and these results correspond with the initial hypothesis. This paper's research results agree with those of literature, such as Liaqat and Ahmed [26] and Wei [30], and show that the methods are robust and stable.…”
Section: Discussionsupporting
confidence: 89%
“…Some empirical studies have focused on the links between rapid household debt growth and financial crises in the advanced world [23,24], and part of this literature has found unconditional negative correlations between household debt changes and future growth based on the panel data of developed and developing countries [8,25]. Liaqat and Ahmed [26] used a panel vector autoregressive model to study the differential effects of components of private debt on income growth for a large panel of countries. The result showed that household debt growth in a given period generally has a positive impact on income and that this effect is much stronger for countries with relatively lower incomes and household debt-to-GDP ratios.…”
Section: Literature Reviewmentioning
confidence: 99%